2020
DOI: 10.1021/acs.energyfuels.0c00220
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of n-Butane to C4 Olefins Using Lattice Oxygen of VOx/Ce-meso-Al2O3 under Gas-Phase Oxygen-Free Conditions

Abstract: High-performance, fluidizable VO x /Ce-meso-Al 2 O 3 catalysts were prepared by an excessive solvent approach. The prepared catalysts were characterized using various physicochemical techniques in order to secure desired properties. XRD, Raman, and FTIR analyses indicated the presence of amorphous VO x phases on Ce-meso-Al 2 O 3 . Nitrogen adsorption isotherm analysis confirmed a mesoporous framework with a high surface area of the catalysts. H 2 -TPR reduction showed an active and stable behavior of the catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The diffraction peaks at 2θ = 28.89 • , 32.38 • , and 47.85 • characterize the cubic crystal structure of the CeO 2 phase, indicating that CeO 2 exists in the cubic fluorite phase. The diffraction peaks of VO x species are absent, possibly because these species are highly dispersed on the surface of the γ-Al 2 O 3 carrier, rendering them undetectable by the XRD instruments [16].…”
Section: Xrd Characterization Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction peaks at 2θ = 28.89 • , 32.38 • , and 47.85 • characterize the cubic crystal structure of the CeO 2 phase, indicating that CeO 2 exists in the cubic fluorite phase. The diffraction peaks of VO x species are absent, possibly because these species are highly dispersed on the surface of the γ-Al 2 O 3 carrier, rendering them undetectable by the XRD instruments [16].…”
Section: Xrd Characterization Resultsmentioning
confidence: 99%
“…phase. The diffraction peaks of VOx species are absent, possibly because these species are highly dispersed on the surface of the γ-Al2O3 carrier, rendering them undetectable by the XRD instruments [16]. The distributions of the Al, V, O, and Ce elements were investigated through mapping energy spectral analysis.…”
Section: Xrd Characterization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation of n -butane with 1 mL feed and 1.0 g of 0.2 wt% Ce-doped VO x / meso -Al 2 O 3 catalyst gave the maximum conversion of 10.6% and 62.3% selectivity of C 4 olefins at 450 °C and 5 s reaction time. 18…”
Section: Heterogeneous Catalysis In Selective Oxidation Reactionsmentioning
confidence: 99%
“…Oxidation of n-butane with 1 mL feed and 1.0 g of 0.2 wt% Ce-doped VO x /meso-Al 2 O 3 catalyst gave the maximum conversion of 10.6% and 62.3% selectivity of C 4 olefins at 450 °C and 5 s reaction time. 18 In 2020, Samek et al reported oxidative dehydrogenation of cyclohexane using alumina-supported VO x -CeO 2 materials. Conversion for cyclohexane to cyclohexene and selectivity for cyclohexene, benzene, CO 2 and CO was studied over CeO 2 and VO x /CeO 2 at 450 °C.…”
Section: Ganapati D Yadavmentioning
confidence: 99%